In aged mice, low surrogate light chain promotes pro‐B‐cell apoptotic resistance, compromises the PreBCR checkpoint, and favors generation of autoreactive, phosphorylcholine‐specific B cells. Issue 3 (27th February 2015) - Ratliff, Michelle; Alter, Sarah; McAvoy, Kelly; Frasca, Daniela; Wright, Jacqueline A.; Zinkel, Sandra S.; Khan, Wasif N.; Blomberg, Bonnie B.; Riley, Richard L.
Summary In aged mice, new B‐cell development is diminished and the antibody repertoire becomes more autoreactive. Our studies suggest that (i) apoptosis contributes to reduced B lymphopoiesis in old age and preferentially eliminates those B‐cell precursors with higher levels of the surrogate light chain (SLC) proteins (λ5/VpreB) and (ii) λ5low B‐cell precursors generate new B cells which show increased reactivity to the self‐antigen/bacterial antigen phosphorylcholine (PC). Pro‐B cells in old bone marrow as well as pro‐B cells from young adult λ5‐deficient mice are resistant to cytokine‐induced apoptosis (TNFα; TGFβ), indicating that low λ5 expression in pro‐B cells is sufficient to cause increased survival. Transfer of TNFα‐producing 'age‐associated B cells' (ABC; CD21/35− CD23−) or follicular (FO) B cells from aged mice into RAG‐2 KO recipients led to preferential loss of λ5high pro‐B cells, but retention of λ5low, apoptosis‐resistant pro‐B cells. In old mice, there is increased reactivity to PC in both immature bone marrow B cells and mature splenic FO B cells. In young mice, absence of λ5 expression led to a similar increase in PC reactivity among bone marrow and splenic B cells. We propose that in old age, increased apoptosis, mediated in part by TNFα‐producing B cells, results in preferential loss of SLChigh pro‐B cells within the bone marrow. Further B‐cell development then occurs via an 'SLClow' pathway that not only impairs B‐cell generation, but promotes autoreactivity within the naïve antibody repertoires in the bone marrow and periphery.